2009
DOI: 10.1302/0301-620x.91b4.22204
|View full text |Cite
|
Sign up to set email alerts
|

The supination deformity and associated deformities of the upper limb in severe birth lesions of the brachial plexus

Abstract: We reviewed 42 consecutive children with a supination deformity of the forearm complicating severe birth lesions of the brachial plexus. The overall incidence over the study period was 6.9% (48 of 696). It was absent in those in Narakas group I (27.6) and occurred in 5.7% of group II (13 of 229), 9.6% of group III (11 of 114) and 23.4% of group IV (18 of 77). Concurrent deformities at the shoulder, elbow, wrist and hand were always present because of muscular imbalance from poor recovery of C5 and C7, inconsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
11
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 15 publications
5
11
1
Order By: Relevance
“…Our study indicated that children with brachial plexus birth palsy are at risk of developing an elbow flexion contracture regardless of the extent of the initial neurological injury, which is inconsistent with previous reports of an association between lesion severity and other sequelae of brachial plexus birth palsy 15,17,[25][26][27] . We had expected to see a greater prevalence of elbow flexion contracture in children with a weak triceps muscle (C7 involvement, or Narakas groups II and III) resulting in elbow flexor-extensor muscle imbalance.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our study indicated that children with brachial plexus birth palsy are at risk of developing an elbow flexion contracture regardless of the extent of the initial neurological injury, which is inconsistent with previous reports of an association between lesion severity and other sequelae of brachial plexus birth palsy 15,17,[25][26][27] . We had expected to see a greater prevalence of elbow flexion contracture in children with a weak triceps muscle (C7 involvement, or Narakas groups II and III) resulting in elbow flexor-extensor muscle imbalance.…”
Section: Discussioncontrasting
confidence: 99%
“…The prevalence of shoulder contracture, glenoid deformity, posterior shoulder dislocation, and forearm supination contracture have been reported to be 56%, 33%, 9%, and 6.9%, respectively [13][14][15] . The prevalence of elbow flexion contracture, however, has yet to be established, with the prevalence in previous reports ranging widely from 4.6% to Disclosure: One or more of the authors received payments or services, either directly or indirectly (i.e., via his or her institution), from a third party in support of an aspect of this work.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 This supinated "beggar's hand" position is associated with poor upper limb function. [3][4][5] Pronation of the forearm, in the presence of a functional hand, is used in more daily activity tasks than supination, such as writing, drinking, and most playing activities.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment ranges from periodic monitoring to neurosurgical repair dependent upon the severity of the injury, the speed of spontaneous recovery, boney changes, and the age of the child (Yam, Fullilove, Sinis, and Fox, 2009).…”
Section: Introductionmentioning
confidence: 99%